Analysing community perceptions on incentive strategies in safeguarding a Malay heritage village: the case of kampung Morten, Melaka - Mat Radzuan, Indera Syahrul; Ahmad, Yahaya (Malaysia Institute of Planners, 2020)
Over-commercialism and the threats posed by uncontrolled development have slowly been eroding the cultural heritage stock, especially in the case of the traditional settlements. This paper reveals the community perceptions and feedbacks on the incentives given in safeguarding the uniqueness of a Malay heritage village known as Kampung Morten in Melaka. This study set out to determine the overarching question, which was, whether the incentive programmes formulated for the community have been found to be suitable to the aspirations and ‘real’ needs of the local communities. Mixed method approaches were used in this study which included document reviews, observations, structured interviews and a questionnaire survey; and involved the residents living in the village. This study evaluates the findings concerning the present policy framework, for understanding and managing the cultural heritage incentives programme in safeguarding the heritage village to establish a sustainable community. This paper has been able to reveal several issues on the conservation incentives policy, most notably of which is the incompatibility of the local communities’ needs with the programme outcomes.